PENGARUH PELAYANAN KOPERASI TERHADAP PARTISIPASI ANGGOTA KOPERASI (KUD) MELATI DESA EMPAT BALAI KECAMATAN KUOK KABUPATEN KAMPAR - Afina, Nur; Sumarno, Sumarno; Suarman, Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack : This study aims to determine the effect of cooperative services to the participation of members. Research was conducted on KUD Jasmine Village Four Halls Districts Kuok District Kampar with 73 sample obtained using the method of probality sampling. The data was collected through simple linear regression analysis techniques. The result showed that the cooperative services has positive affect to the participation of members of the cooperative, (R²) of 0.650. It means, the contribution of cooperative services to the participation of members is 65%. While the rest 35% is another variable that is not examined in this study. Keywords : Service Cooperatives, Member Participation